Does a ban on Islamic veils prevent terrorism in European Union (EU) countries? - Lim, Jia Hui (2019)
As part of an ongoing broader project, this smaller component of Final Year Project looks into whether a ban on Islamic veils prevents terrorism in European Union (EU) countries. Many European countries, especially in Western Europe, have large and growing Muslim minorities. Whilst the vast majority of Muslims in Europe are not involved in radical activities, the realization that certain segments of the European Muslim population may be vulnerable to terrorist radicalization, has sparked security concerns ever since the September 11 attacks in the United States (US) (Archick et al., 2011). Concomitantly, a backlash against Islamic veils is also spreading across the EU. Therefore, this project shall explore the efficacy of bans on Islamic veils in preventing terrorism in EU countries, through theoretical reasoning before progressing on to a case study of France and Spain, which is substantiated by quantitative data collection (mainly via Global Terrorism Database).